Constraint-based Latent Profile Analysis to Investigate the Physical Activity Market Segments among Chinese College Students - Jeeyoon Kim (Journal of Applied Sports Management, 2024)
A segmentation study is conducted via constraint-based latent profile analysis (based on the hierarchical model of leisure constraint), focusing on Chinese college students. Multi-profile analysis further compares key determinants (i.e., constraints/motives) of physical activity intention by profile. Three profiles emerged: ‘body image-conscious physically active’, ‘noncommittal but achievement-driven’, and ‘constrained but motivated by enjoyment/socialization’. Each profile reports distinctive patterns in perceived levels of constraints, motives, and intention. Constraints/motives identified as determinants for intention vary by profile. Compared to North America, China tends to have more college students seeing physical activity as a task than leisure. Profile-specific marketing strategies are suggested.
Keywords: latent profile analysis; physical activity; constraint; motive; market segmentation